PERFORMANCE ANALYSIS OF PORUS ASPHALT MIXTURE USING ANTI-PELALING AGENTS WITH REAM SPECIFICATIONS - Abu, Arman; Desi, Natsar; Gusty, Sri (Universitas Ibn Khaldun Bogor, 2022)
Flexible pavement is very weak against waterlogging because water can loosen the bond between aggregate and asphalt. Porous Asphalt has lower durability because it has high pores so that it can be passed by water. Poor bonding of asphalt and aggregate will cause stripping. This peeling can cause water absorption which will eventually accelerate road damage. Derbo 401 anti-peeling material is one of the new breakthroughs, in the form of additives that can change the properties of aggregates and asphalt, increase adhesion and bonding, and reduce the negative effects caused by water so as to produce a mixture of asphalt with high adhesion. The purpose of this study was to determine the effect of adding anti-stripping agent type Derbo-401 to the permeability value and to determine the resistance of the porous asphalt mixture with the addition of anti-striping agent type Derbo-401 in the Cantabro test and to determine the microstructure of the porous asphalt mixture. Using the REAM-2008 Specification. Based on the results of the study, the Permeability Coefficient Value of the porous asphalt mixture was 0.254 cm3/sec. the lowest percentage Derbo 0.4%, the lowest Cantabro Loss value at 0.3% addition percentage gets an average value of 6.13%, Has met the required specifications max 15%. The elements that make up the porous asphalt mixture with the addition of Derbo percentage are more in the elements Si (silicon) 19.93%, Ca (calcium) 21.12%, S (sulfur) 8.45%, Fe (ferrum) 8.80%, K (potassium) 2.42% and the other elements are less.